Pathogenesis Markers of Hashimoto's Disease—A Mini Review - Binghui Jin; Shuang Wang; Zhe Fan (Frontiers in Bioscience-Landmark, 2022)
Hashimoto’s thyroiditis (HT) is the most common autoimmune disease involving the thyroid gland. HT often clinically manifest as hypothyroidism due to the destruction of thyroid cells mediated by humoral and cellular immunity. The pathogenesis of HT is a complex process in which environmental factors, hereditary inclination, trace elements immune factors, cytokines, and DNA and miRNA all play an important role. Herein, we summarize the precision factors involved in the pathogenesis of HT and offer an update over the past 5 years to provide a theoretical basis for further investigation of the relevant targets for HT treatment.